Investigation on the Services of Private Cloud Computing by Using ADAM Method - Nur Widiyasono; Imam Riadi; Ahmad Luthfie (Institute of Advanced Engineering and Science, 2016)
Cloud services are offered by many cloud service providers, but in for large companies generally are build by a private cloud computing. In cloud systems of abuse it can be done by internal users or due to misconfiguration or may also refer to weaknesses in the system. This study evaluated the ADAM method (Advanced Data Acquisition Model) and tested the case schemes which are being carried out in the laboratory simulation of the process in order to obtain forensic evidence of digital data on private cloud computing services. Referring to the results of the investigation process by using ADAM Method, it can be verified that there are several parameters of the success investigation including the structure of files, files, time stamp, mac-address, IP address, username password, and the data from a server both from the desktop PC or smartphone, therefore the investigation by using ADAM can be succesed properly and correctly. Another contribution of this study was to identify the weaknesses of the service system that used owncloud in users list of the the same group can change another’s user’s passwod.